Análisis comunicacional de los impactos de la campaña quiero andar tranquila, calles sin acoso en el trolebús, período octubre – diciembre 2011 - Garzón Macías, Gladys Fernanda (2015)
This research addresses the most important aspects to be considered carefully in terms of violence exists today against female persons, taking into consideration the characteristics of Ecuador's patriarchal society and rooting customs that relegate woman background on issues of sexuality, limiting it to play a secondary role in sharing and giving men the role of the approach to the same situation that has led to the harassment of women and public places such as workplaces and transport public and others. Sexual harassment is now justified and confused with attention and compliments provided to women since ancient times, being such samples demonstrations of respect and admiration for women and no disrespect and abuse, key features of sexual harassment, a situation in which the man backed by his strength, status and impunity in situations such abuses and marginalizes women, resulting in the same situation of psychological imbalance that adversely affects their social and individual development, hence the importance of spreading awareness campaigns, denunciation and support to women's rights to be respected in all spaces and social areas as the campaign “Quiero andar tranquila, calles sin acoso” In the trolleybus, which when analyzed from the standpoint of communication, says the value and impact of such actions and also reveals the entrenchment of macho attitudes and disregard for women as a result of a patriarchal culture in which man has the role of judge and regulatory initiatives and sexual attitudes.